PENCEGAHAN PENULARAN VIRUS COVID-19 PADA ERA NEW NORMAL DI DESA CIASMARA, KECAMATAN PAMIJAHAN, BOGOR - Rully Trihantana; Ria Kusumaningrum; Amelia Oktaviani (SAHID DEVELOPMENT JOURNAL, 2022)
The increasing number of positive people affected by the corona virus in Indonesia shouldincrease public awareness of the dangers of this outbreak. The purpose of this activity is toimplement the Covid-19 prevention agreement, take precautions and prevent the spread of Covid19,and disseminate information about Covid-19 in the form of inviting  public participation  and raisin awareness. The preparation stages are as follows: Observation, extracting public knowledge related to Covid-19 by interviewing the public and crowds, surveying locations to put up posters related to Covid-19 information, and making posters that are attractive, easy to read  and understand for the public. The Covid-19 pandemic is a serious problem that must be resolved  immediately. Masks are used to minimize the spread of the virus from person to person. The high demand for masks, especially medical masks, has limited market demand. Therefore, cloth masks are needed as a substitute for the community so that they can be used in daily activities to deal with the health crisis that occurs. The purpose of this community service activity is to providepublic awareness of the importance of wearing masks during new normal conditions and to carryout 1,000 masks movement activities for the community. This activity is in collaboration withFamily Welfare Education in Ciasmara Village, Pamijahan District, Bogor. This activity was alsocarried out by socializing to the public about the importance of using masks and hand sanitizers.